Um modelo de risco de crédito para o setor bancário de Fortaleza - Lima, Marcus Vinícius Pereira (2012)
The paper develops a tool for modeling the bank credit risk and applies this to banking market of Fortaleza. Using data from a large commercial bank of the city for 290 customers with active accounts and minimum income of six hundred reais, were selected 23 control variables and was estimated the probability of default on the modalities check and other credit restrictions. The results showed that: i) females are less likely to face restrictions, although this is not a determinant of emissions of bad checks; ii) people who have insurance contracted with the bank showed themselves more likely to default and iii) the extent of the bank rating proposal was effective in measuring the chance of credit risk.